Lipid-polymorphism of plant thylakoid membranes. Enhanced non-bilayer lipid phases associated with increased membrane permeability - Ughy, Bettina; Karlický, Václav; Dlouhý, Ondřej; Javornik, Uroš; Materová, Zuzana; Zsiros, Ottó; Šket, Primož; Plavec, Janez; Špunda, Vladimír; Garab, Győző (Physiologia plantarum, 2019)
Earlier experiments, using 31 P-NMR and time-resolved merocyanine fluorescence spectroscopy, have shown that isolated intact, fully functional plant thylakoid membranes, in addition to the bilayer phase, contain three non-bilayer (or non-lamellar) lipid phases. It has also been shown that the lipid polymorphism of thylakoid membranes can be characterized by remarkable plasticity, i.e. by significant variations in 31 P-NMR signatures. However, changes in the lipid-phase behaviour of thylakoids could not be assigned to changes in the overall membrane organization and the photosynthetic activity, as tested by circular dichroism and 77 K fluorescence emission spectroscopy and the magnitude of the variable fluorescence of photosystem II, which all showed only marginal variations. In this work, we investigated in more detail the temporal stability of the different lipid phases by recording 31 P-NMR spectra on isolated thylakoid membranes that were suspended in sorbitol- or NaCl-based media. We observed, at 5°C during 8 h in the dark, substantial gradual enhancement of the isotropic lipid phases and diminishment of the bilayer phase in the sorbitol-based medium. These changes compared well with the gradually increasing membrane permeability, as testified by the gradual acceleration of the decay of flash-induced electrochromic absorption changes and characteristic changes in the kinetics of fast chlorophyll a-fluorescence transients; all variations were much less pronounced in the NaCl-based medium. These observations suggest that non-bilayer lipids and non-lamellar lipid phases play significant roles in the structural dynamics and functional plasticity of thylakoid membranes.
Keywords: Thylakoids; Photosystem II Protein Complex; intracelulární membrány; Lipid Bilayers; lipidové dvojvrstvy; kinetika; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; tylakoidy; Intracellular Membranes; Kinetics; fotosystém II (proteinový komplex)